Desorption of Indigosol Blue from Humic Acid Coated Fe3O4 Particles - Latifah, Wachidah Nur; Rahmayanti, Maya (Proceeding International Conference on Science and Engineering, 2020)
Desorption of indigosol blue from humic acid coated Fe3O4 (Fe3O4-HA) was investigated. The desorption had been done with HCl as desorption agent. The purpose of this study was to determine the effect of various concentration HCl on desorption efficiency of indigosol blue from Fe3O4-HA. Desorption was carried out during 60 minutes of contact time.The result confirmed that HCl can be used as desorption agent although complete desorption can not be achieved, the desorption efficiency was 48.52 % with concentration of HCl 1 M.